Investigation of the Methodology and Environmental Importance of Incinerators in Disposing of Hazardous Waste in Afghanistan - Mujeeb, Mujeebullah; Sherzad, Mohammad Dawood (Journal of Natural Sciences – Kabul University, 2022)
Daily waste management in Afghanistan's cities is one of the most pressing environmental issues today. Incinerators are vital modern technological solutions for the proper disposal of hazardous waste. Advanced Combustion System (ACS) incinerators and other similar models that comply with European and American environmental standards have been introduced to the global market, showing favorable results in the disposal of clinical waste. Over the past decade, international military forces in Afghanistan have used incinerators imported by JS International, URS Corporation, and USFOR-A to manage hazardous clinical waste at their bases in the country. These incinerators have proven to be effective in reducing the environmental impact of clinical waste disposal.